2011
DOI: 10.1016/j.jmb.2011.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hydrophobic Interactions to Protein Stability

Abstract: Our goal was to gain a better understanding of the contribution of hydrophobic interactions to protein stability. We measured the change in conformational stability, Δ(ΔG), for hydrophobic mutants of four proteins: villin head piece subdomain (VHP) with 36 residues, a surface protein from Borrelia burgdorferi (VlsE) with 341 residues, and two proteins previously studied in our laboratory, ribonucleases Sa and T1. We compare our results with previous studies and reach the following conclusions. 1. Hydrophobic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
242
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 351 publications
(260 citation statements)
references
References 100 publications
(144 reference statements)
17
242
0
1
Order By: Relevance
“…28 Protein folding is driven in large part by hydrophobic association, and protein sequences generally require a threshold level of hydrophobicity to fold stably into a compact structure, [29][30][31][32] but simple protein models suggest that excessively hydrophobic sequences are less likely to fold uniquely. 28,[33][34][35] High or increased hydrophobicity is experimentally associated with chameleon sequences, lowered structural specificity, or outright fold changes in a number of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…28 Protein folding is driven in large part by hydrophobic association, and protein sequences generally require a threshold level of hydrophobicity to fold stably into a compact structure, [29][30][31][32] but simple protein models suggest that excessively hydrophobic sequences are less likely to fold uniquely. 28,[33][34][35] High or increased hydrophobicity is experimentally associated with chameleon sequences, lowered structural specificity, or outright fold changes in a number of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have described the physical and thermodynamic consequences of altering the hydrophobic core of both the C-terminal subdomain [1][2][3][4][5][6]13 and more recently the N-terminal subdomain 7 of villin headpiece. In the studies of the C-terminal subdomain, it has been demonstrated that even relatively small perturbations within the hydrophobic core are of significant thermodynamic consequence.…”
Section: Discussionmentioning
confidence: 99%
“…The $3.3 kcal/mol destabilization of the L61G point mutation can be explained by the loss of the hydrophobic interface between leucine 61 and the residues comprising hydrophobic pocket ($1.1 6 0.5 kcal/mol per ACH 2 A group). 13 The loss of $3.5 kcal/mol between the L61[GL] and the wild-type construct is likely due to the conformational strain imposed by transforming the Cterminal end of helix 4 from an a-helix into p-helix. It is interesting that 3.5 kcal/mol destabilization is very close to the 3.3 kcal/mol destabilization attributable to the loss of the hydrophobic interface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations